Distribution of genetic polymorphisms associated with hepatitis C virus (HCV) antiviral response in a multiethnic and admixed population - Trinks, Julieta (2014)
The prevalence of genetic polymorphisms identified as predictors of therapeutic-induced hepatitis C virus (HCV) clearance differs among ethnic groups. However, there is a paucity of information about their prevalence in South American populations, whose genetic background is highly admixed. Hence, single-nucleotide polymorphisms rs12979860, rs1127354 and rs7270101 were characterized in 1350 healthy individuals, and ethnicity was assessed in 259 randomly selected samples. The frequency of rs12979860CC, associated to HCV treatment response, and rs1127354nonCC, related to protection against hemolytic anemia, were significantly higher among individuals with maternal and paternal Non-native American haplogroups (64.5% and 24.2%), intermediate among admixed samples (44.1% and 20.4%) and the lowest for individuals with Native American ancestry (30.4% and 6.5%). This is the first systematic study focused on analyzing HCV predictors of antiviral response and ethnicity in South American populations. The characterization of these variants is critical to evaluate the risk–benefit of antiviral treatment according to the patient ancestry in admixed populations.